De l'accompagnement des pratiques au contrôle des enseignants : quels enjeux pour quel métier ? - Marie-Ange Barthassat; Danielle Bonneton (Nantes Université, 2010)
Starting from a series of interviews carried out with teachers who were involved in the educational reform of the Geneva elementary school (1994-1999), this article tries to demonstrate in what way individual as well as collective learning took place during that period. Furthermore, it aims at defining to what extent the rigourous coaching design, as it was conceived at that time helped accompanying teacher pratices is necessary. The working hypotheses are embedded in research traditions focusing on the link between research and practice, or action research, adopting a constructivist and systemic perspective: the key idea being to obtain the adherence of all actors involved through articulated communication processes, exchange networks, and the reading and writing about the work and the organisation of school work. The research questions concerned progression of the actors in a logic of Learning Organization, their relation to theory, its articulation to practice, to constructed knowledge, to inherited traces which are visible today, in order to identify some lasting significant appropriations of professionalization, beyond nostalgic or ambiguous evocations. As it is underlined by a teacher - « certain conditions are needed, in order to seize theory » - theory being a lever as well as an impediment. Furthermore, some aspects of the current control of teacher's work activities are discussed in relation to processes of decentralization. These aspects question the relevance of a claimed professional development and, as such, the definition of the "métier".